Aortic root longitudinal strain by speckle-tracking echocardiography predicts progressive aortic root dilation in Marfan syndrome patients. (8th February 2021) - Guala, A; Pons, MI; Ruiz-Munoz, A; Dux-Santoy, L; Madrenas, L; Valente, F; Lopez-Sainz, A; Galian, L; Gutierrez, L; Sao-Aviles, A; Gonzalez-Alujas, T; Ferreira, I; et al.
Abstract: Funding Acknowledgements: Type of funding sources: Public grant(s) – National budget only. Main funding source(s): Spanish Ministry of Science, Innovation and Universities; Instituto de Salud Carlos III Introduction: In Marfan syndrome (MFS) patients reduced longitudinal strain of the ascending aorta (AAo) as measured by applying feature-tracking on cine cardiac magnetic resonance (CMR) images predicts aortic root dilation and aortic events during the follow-up. Speckle-tracking is well established for cardiac deformation assessment but proximal aorta applications are challenging due to limited wall thickness and substantial cardiac motion. Moreover, echocardiography is widely used in the clinical assessment aortic diseases. Purpose: We aimed to test a speckle-tracking tool for root longitudinal strain analysis in terms of comparison with CMR-derived AAo longitudinal strain and reproducibility and as predictor of dilation in MFS patients. Methods: Thirty-five MFS patients diagnosed by original GHENT criteria, with maximum aortic root diameter of 45 mm and free from previous aortic dissection or cardiac/aortic surgery and non-severe aortic regurgitation were consecutive enrolled and followed-up. CMR and echocardiography were performed less than 2 months apart. Baseline and final aortic root diameter were measured on CMR images. To quantify aortic root cyclic elongation by echocardiography, two regions of interests were manually created covering both walls in a parasternal long-axis view and tracked along the cardiac cycle (Figure 1). Longitudinal strain was computed as the average of maximum increase in relative distance of several sub-regions covering both walls. CMR-derived AAo longitudinal strain was available in 29 patients. Intra-observer reproducibility was tested in 15 patients via intraclass correlation coefficient (ICC) for single-rater absolute agreement. Results: Aortic root longitudinal strain by echocardiography was mildly related to CMR-derived AAo longitudinal strain (R = 0.27) and was larger compared to CMR-derived values (16.2 ± 6.0 vs 11.3 ± 4.3). Reproducibility was high, with ICC of 0.811, R = 0.802, p < 0.001. After a mean follow up of 76 ± 13 months, aortic root diameter grew in 20 patients with a rate of 0.29± 0.24 mm/year. Overall mean growth-rate was 0.87 ± 0.33 mm/year. In multivariable analysis corrected for age and baseline aortic root diameter, baseline longitudinal strain by echocardiography was independently and inversely related to progressive dilation (p = 0.033). Conclusions: The measurement of aortic root longitudinal strain by speckle-tracking echocardiography is feasible. Aortic root longitudinal strain is an independent predictor of progressive dilation in MFS patients. This may permit the improvement of risk-stratification in aortic diseases in large scale studies.